2016
DOI: 10.1186/s12863-016-0419-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of variation in lifespan using a multiparental advanced intercross Drosophila mapping population

Abstract: BackgroundConsiderable natural variation for lifespan exists within human and animal populations. Genetically dissecting this variation can elucidate the pathways and genes involved in aging, and help uncover the genetic mechanisms underlying risk for age-related diseases. Studying aging in model systems is attractive due to their relatively short lifespan, and the ability to carry out programmed crosses under environmentally-controlled conditions. Here we investigate the genetic architecture of lifespan using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…In addition to Marriage et al (2014), various studies have identified very large effect QTL with the DSPR (KING et al 2012b;COGNI et al 2016), and for such QTL finding and validating the causative locus using the battery of tools available for D. melanogaster is within reach. However, QTL effects are typically more modest (KISLUKHIN et al 2013;HIGHFILL et al 2016), often do not implicate unambiguous candidates, and may regularly be generated by noncoding variants (ALBERT AND KRUGLYAK 2015). Such features ensure that some fraction of causative variants will always remain uncharacterized.…”
Section: Resolving Causative Polymorphisms Underlying Qtlmentioning
confidence: 99%
“…In addition to Marriage et al (2014), various studies have identified very large effect QTL with the DSPR (KING et al 2012b;COGNI et al 2016), and for such QTL finding and validating the causative locus using the battery of tools available for D. melanogaster is within reach. However, QTL effects are typically more modest (KISLUKHIN et al 2013;HIGHFILL et al 2016), often do not implicate unambiguous candidates, and may regularly be generated by noncoding variants (ALBERT AND KRUGLYAK 2015). Such features ensure that some fraction of causative variants will always remain uncharacterized.…”
Section: Resolving Causative Polymorphisms Underlying Qtlmentioning
confidence: 99%
“…Given the well‐known association between longevity and fecundity, it is interesting to test these two classes of traits for their possible associations to heat‐resistance genotypes at elevated temperature (e.g., Loeschcke et al., ). QTL mapping in recombinant inbred lines (RIL) from crosses between heat‐selected populations provided information about genomic regions affecting heat resistance (Norry et al., , 2007a, ; Morgan & Mackay, ; Arias et al., ; Sambucetti et al., ), as well as longevity and fecundity (Defays et al., ; Sambucetti et al., ; Highfill et al., ). This information can be used to establish fly stocks with alternative genotypes for heat resistance, which can be used to test fitness‐related traits of individuals carrying heat‐sensitive genotypes in comparison to individuals carrying heat‐resistant genotypes (e.g., Loeschcke et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A. Distribution of mean female lifespan in DSPR pB RILs (Highfill et al (2016). RILs with low female starvation resistance (in the bottom 25% of the distribution) are shown in solid black symbols, while other RILs are shown in gray.…”
mentioning
confidence: 99%